Unstable chromosome aberrations do not accumulate in normal human fibroblast after fractionated x-irradiation. - Mitsuaki Ojima; Maki Ito; Keiji Suzuki; Michiaki Kai (PLoS ONE)
We determined the frequencies of dicentric chromosomes per cell in non-dividing confluent normal human fibroblasts (MRC-5) irradiated with a single 1 Gy dose or a fractionated 1 Gy dose (10X0.1 Gy, 5X0.2 Gy, and 2X0.5 Gy). The interval between fractions was between 1 min to 1440 min. After the completion of X-irradiation, the cells were incubated for 24 hours before re-plating at a low density. Then, demecolcine was administrated at 6 hours, and the first mitotic cells were collected for 42 hours. Our study demonstrated that frequencies of dicentric chromosomes in cells irradiated with a 1 Gy dose at different fractions were significantly reduced if the fraction interval was increased from 1 min to 5 min (p<0.05, χ2-test). Further increasing the fraction interval from 5 up to 1440 min did not significantly affect the frequency of dicentric chromosomes. Since misrejoining of two independent chromosome breaks introduced in close proximity gives rise to dicentric chromosome, our results indicated that such circumstances might be quite infrequent in cells exposed to fractionated X-irradiation with prolonged fraction intervals. Our findings should contribute to improve current estimation of cancer risk from chronic low-dose-rate exposure, or intermittent exposure of low-dose radiation by medical exposure.